IMPLEMENTASI SISTEM PEMANTAUAN INTENSITAS CAHAYA DENGAN IOT DI PLANT FACTORY KEBUN PERCOBAAN FAKULTAS PERTANIAN UNIVERSITAS UDAYAN - Aveliano Tandrianto; I Nyoman Setiawan; A. A. Ngurah Amrita (Program Studi Teknik Elektro UNUD, 2022)
Plant factory is a plant warehouse with a closed planting maintenance system which is expected to overcome the problem of pest attack and disturbance of climatic factors. In this study, an IoT-based light intensity monitoring system has been designed at the Plant Factory, Experimental Garden, Faculty of Agriculture, Udayana University. To monitor the value of the LED light intensity. The hardware used in this study uses 2 microcontrollers, namely arduino nano and ESP 32, using a BH1750 sensor to measure the intensity of light lux and using RTC to calculate the time on the device. All hardware components are assembled in parallel and become an IoT system, which is one way to be able to carry out automatic monitoring and control of lights that can be done anywhere. Monitoring with IoT at the plant factory using the internet which can be accessed through the blynk application. With this technology, it is expected to be able to regenerate farmers in the future to farm using IoT technology, the concept of hoeing and plowing, becoming more modern farming.